Human placental mesenchymal stromal cell‐derived small extracellular vesicles as a treatment for severe COVID‐19: A double‐blind randomized controlled clinical trial - Mohammad Hossein Zamanian; Amir Hossein Norooznezhad; Zohreh Hosseinkhani; Daryoush Hassaninia; Feizollah Mansouri; Siavash Vaziri; Mehrdad Payandeh; Fatemeh Heydarpour; Sara Kiani; Maria Shirvani; Mojgan Rajati; Mitra Bakhtiari; et al. (Journal of Extracellular Vesicles, 2024)
Abstract The current study aimed to investigate the effects of human placental mesenchymal stromal cell‐derived small extracellular vesicles (hPMSC‐sEVs) as a treatment for COVID‐19. This double‐blind, randomized, controlled clinical trial was conducted on two groups of patients with COVID‐19‐associated acute respiratory distress syndrome. After randomization, the control group received standard treatment and placebo, and the intervention arm received standard treatment plus hPMSC‐sEVs. The number of hospital deaths was considered the primary outcome. After meeting the exclusion and inclusion criteria, 21 and 24 patients were allocated to intervention and control arms, respectively. Besides admission SpO2 levels, which were significantly lower in the intervention arm (p = 0.008), all the baseline demo‐biographic and laboratory variables were similar between the groups. It was shown that hPMSC‐sEVs could significantly (p = 0.015) decrease the mortality ratio in the intervention group (4/21 [19.04%]) compared to the controls (13/24 [54.16%]). The mean time to death in the intervention and control groups was 28.06 and 11.10 days, respectively (p < 0.001). This study showed that hPMSC‐sEVs are a possible treatment for critically ill patients with COVID‐19.